2018
DOI: 10.5606/tgkdc.dergisi.2018.15391
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of aortic arch aneurysms: Open surgery or hybrid procedure?

Abstract: ÖZAmaç: Bu çalışmada arkus aort anevrizmalarının tedavisinde hibrid işlem ve açık cerrahi sonuçları karşılaştırıldı.Ça lış mapla nı:Ocak 2004 -Ocak 2010 tarihleri arasında arkus aort anevrizması nedeniyle total arkus aort replasmanı yapılan 26 hasta (21 erkek, 5 kadın; ort. yaş 56.6±12.4 yıl; dağılım, 20-83 yıl) retrospektif olarak değerlendirildi. Hastalar açık konvansiyonel cerrahi grubu (grup 1, n=15) ve hibrid işlem (aynı seansta total arkus aort debranching ve endovasküler stent implantasyonu) grubu (grup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…When assessing short-term mortality, 10 of the 12 studies (Table 6) evaluated operative mortality, in-hospital mortality, or 30-day mortality. All studies found no difference in short-term mortality, [17][18][19][20][21][22][23][25][26][27] and these findings persisted in studies that performed matching. 18,20,22 Short-term mortality across all studies ranged from 0% to 30% in the open operation cohort and 0% to 23% in the hybrid operation cohort.…”
Section: Short-term Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…When assessing short-term mortality, 10 of the 12 studies (Table 6) evaluated operative mortality, in-hospital mortality, or 30-day mortality. All studies found no difference in short-term mortality, [17][18][19][20][21][22][23][25][26][27] and these findings persisted in studies that performed matching. 18,20,22 Short-term mortality across all studies ranged from 0% to 30% in the open operation cohort and 0% to 23% in the hybrid operation cohort.…”
Section: Short-term Mortalitymentioning
confidence: 99%
“…When reviewing LOS, 9 of the 12 studies (Table 5) evaluated LOS among patients undergoing conventional open approach compared to those undergoing hybrid approach. [17][18][19][20]22,[24][25][26][27] We have divided these studies into those evaluating hospital LOS and intensive care unit (ICU) LOS (Table 5). Hospital LOS was shorter in patients undergoing hybrid arch replacement compared to open in most studies, [18][19][20]24,25 while few studies found no difference, 22,26 and no studies found hybrid arch replacement to be associated with longer hospital LOS.…”
Section: Length Of Staymentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, TEVAR can be an option if reentry tears are wished to be closed afterward. 7 In light of all these knowledge, we assume that indications of elephant trunk procedures cover a limited patient population.…”
mentioning
confidence: 99%